Strategi Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Karawang Dalam Mitigasi Bencana Banjir di Desa Sukamakmur - Vina Oktavia; Evi Priyanti; Rahman Rahman (Journal of Management and Social Sciences, 2026)
This study aims to examine flood disaster mitigation efforts carried out by the Regional Disaster Management Agency in Sukamakmur Village, Karawang Regency. This research employed a qualitative method with a case study approach. The theory used in this study is the Strategy Theory proposed by James Brian Quinn (2003:10), which consists of three dimensions: objectives, policies, and programs. The study identifies problems related to flood disasters that occur almost every year in Sukamakmur Village. To address these issues, it is necessary to analyze the mitigation efforts implemented by the Regional Disaster Management Agency (BPBD), as well as the related policies and programs concerning flood disasters. The findings show that the objective of disaster mitigation is directed toward improving community preparedness and capacity in dealing with flood risks. Mitigation policies are implemented through strengthening community capacity based on non-structural mitigation, such as the establishment of Disaster Resilient Villages (DESTANA), village disaster volunteers, and disaster risk assessments. The mitigation programs carried out include disaster awareness socialization, mitigation training, and dissemination of daily weather information. In its implementation, BPBD also coordinates with the village government, sub-district task forces, and the River Basin Management Agency (BBWS). These mitigation programs have had a positive impact on increasing community knowledge, preparedness, and participation, although there are still obstacles in the form of limited budgets, infrastructure, human resources, and suboptimal cross-sector coordination. The contribution of this research is to provide additional insight and new information regarding the role of the Regional Disaster Management Agency in flood disaster mitigation.